UNITED STATES’ UNWAVERING SUPPORT TO ISRAEL: BIASED FOREIGN POLICY IN ISRAEL-PALESTINE CONFLICT UNDER PRESIDENT DONALD TRUMP’S ADMINISTRATION (2016-2019) - Soekarno, Anisah Amalia; Utomo, Tri Cahyo (Journal of International Relations, 2019)
Human Rights has been a prominent topics in contemporary international relations. The United States has long been a leader in the development and enforcement of international Human Rights regime. But there are controversies on how The U.S. conduct its policies related to Human Rights. The international society has acknowledge U.S.’ double standard practices. This kind of attitudes can be found in regard of U.S. policy in Israel-Palestine conflict. For many years, despite its support towards human rights, the U.S. has been biased favoring Israel which reflected in its foreign policy related to this matter. The U.S. has supports whatever Israel do, backing its leader’s actions, and even protecting Israel from the accusation of Human Rights violations in international arena. This biased attitudes are far deeper under President Donald Trump’s administration. This research aims to analyze why this attitude happen and try to explain factors behind biased foreign policy conducted by the U.S. regarding Israel-Palestine conflict. This research will use Neoclassical Realism’s perspective in analyzing the factors behind U.S. unwavering supports towards Israel. The result of this research indicates that the U.S.’ foreign policy is influenced by systemic as well as domestic factors, which help to explain its biased attitudes in Israel-Palestine conflict that favor Israel.